2012
DOI: 10.1021/la300871q
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Dynamics, and Lubrication of MoS2 Platelets and Nanotubes

Abstract: A model is introduced to investigate structure, stability, dynamics, and properties of MoS(2). The tribological behavior of the material is obtained from the autocorrelation function, ACF, of the forces, using the Green-Kubo equation, and by the classical Amontons' laws. In the idealized system, i.e. without defects, junctions, vacancies, asperities, and impurities, both models find a superlubrication regime, in agreement with some experiments. In nanotubes, NTs, friction is an order of magnitude lower than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 40 publications
0
43
0
4
Order By: Relevance
“…All the chemical reagents used in this work were analytical grade, including Na 2 MoO 4 Á 2H 2 O, thioacetamide (TAA), hydrochloric acid (HCl), ethanol, and dioctyl sebacate (DOS, C 26 ϕ10 mm, 3 mm in thickness, GCr15 steel, 190-210 HV30 in hardness, 0.014 um in surface roughness) was provided by the Jinan YiHua Tribology Testing Technology Co., Ltd., China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the chemical reagents used in this work were analytical grade, including Na 2 MoO 4 Á 2H 2 O, thioacetamide (TAA), hydrochloric acid (HCl), ethanol, and dioctyl sebacate (DOS, C 26 ϕ10 mm, 3 mm in thickness, GCr15 steel, 190-210 HV30 in hardness, 0.014 um in surface roughness) was provided by the Jinan YiHua Tribology Testing Technology Co., Ltd., China.…”
Section: Methodsmentioning
confidence: 99%
“…With advanced chemical techniques, MoS 2 with these novel morphologies has been synthesized [14][15][16][17][18]. The applications of spherical IF-MoS 2 [19][20][21][22] and MoS 2 nanotubes [23][24][25][26] also enrich the lubricating mechanisms of solid lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well known that MoS 2 nanoparticles are among the most common lubricant additive due to a layered and two-dimensional structure with weak van der Waals forces between its molecular layers and strong interlayer covalent bonds. Its efficacy for tribological applications was demonstrated in many reports [12][13][14]. Previous studies revealed that the lubrication performance of MoS 2 nanoparticles was not only dependent on quantity, the morphology, size and crystal structure but also the contact surfaces [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum disulphide (MoS2) is widely used as a dry film solid lubricant [6,11] due to its laminar hexagonal structure which results in low coefficients of friction being observed [12,13]; in many industrial sectors, the MoS2 is often applied to a surface as a coating in the form of MoS2 particles in a polymeric binder [14] (although MoS2 can be utilized as a low friction material in a wide range of forms [15][16][17][18][19]). In the case of a polymer loaded with MoS2 particles, the coating is often applied on top of a metallic bond layer (typically Cu-Ni-In) [20] which is itself deposited onto the component surface by thermal spraying.…”
Section: Introductionmentioning
confidence: 99%